2020
DOI: 10.1051/sicotj/2020032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disc degeneration adjacent to AOspine A fractures: pre- and post-operative MRI analysis

Abstract: Introduction: The management of type A thoracolumbar fractures varies from conservative treatment to multiple level fusion. Indeed, although Magerl defined the type A fracture as a strictly bone injury, several authors suggested associated disc lesions or degeneration after trauma. However, the preservation of mobility of the adjacent discs should be a major issue. This study was conducted to analyze the presence of immediate post-traumatic disc injuries and to know if discs degenerate after receiving treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…By comparing different types of iodized oil deposition in patients, we found that there were marked differences in clinical prognosis. Patients with a large area and uniform distribution of iodized oil deposition had a lower incidence of new lesions and better prognosis after surgery ( 22 , 23 ). Moreover, TACE is more effective than conventional chemotherapy in advance PHC treatment compared, which could effectively improve the tumor focuses of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing different types of iodized oil deposition in patients, we found that there were marked differences in clinical prognosis. Patients with a large area and uniform distribution of iodized oil deposition had a lower incidence of new lesions and better prognosis after surgery ( 22 , 23 ). Moreover, TACE is more effective than conventional chemotherapy in advance PHC treatment compared, which could effectively improve the tumor focuses of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Its advantage over internal xation may therefore be the reduction of complications related to the instrumentation (rob breakage, infection, screw loosening…) and leaving free the discs adjacent to the fracture [10,11]. Additionally, Magerl A fractures have been described as strictly bony fractures, and the proper reduction of the vertebral body reduction seems to reduce the risk of secondary disc degeneration [12,13]. However, most of the available device only allow one try for the corporeal reduction, device with a nonrepeatable reducing movement and does not allow to target the area to be reduced.…”
Section: Introductionmentioning
confidence: 99%